Intrathoracic extramedullary hematopoiesis as a posterior mediastinal tumor: a case report - Ersöz Köse, Elçin; Reyhan, Gökay; Kanbur Metin, Serda; Evman, Serdar; Tezel, Çağatay; Yalçınkaya, İrfan (The European Research Journal, 2018)
Extramedullary hematopoiesis (EMH) is a rare disorder, defined as the appearance of hematopoietic elements outside the bone marrow or peripheral blood. Usually it is diagnosed incidentally and very rarely it presents as a posterior mediastinal mass clinically mimicking with many other benign or malignant mediastinal tumors. Intrathoracic EMH is a rare condition and only very few case reports have been described in patients with chronic myeloproliferative disorders specially myelofibrosis with myeloid metaplasia and spherocytic anemias. The paravertebral area is an uncommon site for EMH, with the possible exception of sporadically reported intrathoracic manifestations. In this study, a 38-year-old male patient was followed for myeloproliferative disease. Tumor-like lesions at the bilateral posterior mediastinum were detected in the patient who applied to our clinic due to fall. Excision was planned with video- assisted thoracoscopic surgery to differentiate from mediastinal tumors, but the mass unblock was removed with posterolateral thoracotomy because of the appearance of the lesion and large size. Histopathologic diagnosis was reported as extramedullary hematopoiesis. Patient was presented because of its rare location.